ORGANISATIONAL AND ECONOMIC MECHANISMS FOR SMALL AND MIDDLE ENTREPRENEURSHIP STIMULATION IN THE ARCTIC - Shikverdiev, Arif; Vishnyakov, Andrey; Oganezova, Nina; Obrezkov, Nikita; Pleshev, Dmitriy (Revista Inclusiones, 2020)
The paper analyses the issues of small and medium entrepreneurship development in the Arctic environment and proposes ways to solve them. The proposed mechanisms of organisational and economic stimulation of small and medium entrepreneurship in the Arctic refer to the theoretical and institutional foundations considering not only the elements of market relations but also — given the features of the Arctic — the principal role of the state. The methodology and capabilities of government stimulation of small and medium entrepreneurship in the Arctic are employed, as well as innovation-driven approaches, particularly the development of Arctic venture as a specific instrument. An analysis of the developmental factors of small and medium entrepreneurship in the Arctic environment highlights the governance aspects, particularly, the major role of efficient public, municipal and corporate governance, as well as the need to improve social and environmental responsibility standards. The possibility of establishment of special (free) economic zones is substantiated with a view to transforming the Arctic areas as a special tax and administrative zone and easing the conditions of doing business.